2011
DOI: 10.5367/te.2011.0071
|View full text |Cite
|
Sign up to set email alerts
|

The Calculation Approach for Leakages of International Tourism Receipts: The Turkish Case

Abstract: Savings, taxes and imports, known as leakages, decrease the stimulus effect of new dollars in an economy. This study presents an applicable framework for calculating the net international tourism receipts of Turkey by eliminating leakages through an application of the satellite accounts approach, based on input–output tables. According to the results, the proportion of tourism income leakage for Turkey is estimated at 38.5%. Although this proportion is within the limits proposed by the World Tourism Organizati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…Some scholars have also highlighted that economic leakages in the tourism industry can occur through repatriated profits of multinational hotels and savings from salaries of foreign management and employees (Ünlüönen, Kiliçlar, & Yüksel, 2011). However, this applies only in the more development destinations such as Guam and Fiji who have a significant number of foreign-owned internationally branded hotels (Harrison & Pratt, 2013).…”
Section: Theme 3-economic Linkages and Leakagesmentioning
confidence: 99%
“…Some scholars have also highlighted that economic leakages in the tourism industry can occur through repatriated profits of multinational hotels and savings from salaries of foreign management and employees (Ünlüönen, Kiliçlar, & Yüksel, 2011). However, this applies only in the more development destinations such as Guam and Fiji who have a significant number of foreign-owned internationally branded hotels (Harrison & Pratt, 2013).…”
Section: Theme 3-economic Linkages and Leakagesmentioning
confidence: 99%
“…One common limitation noted in most IO/SAM studies of tourism is that the basis for analysis is provided either by the most recent available data covering a single calendar year (Kim and Kim, 2015; Ünlüönen et al, 2011) or by a comparison of data from two calendar years separated by a gap which may be several years in length (Sun and Wong, 2014; Surugiu, 2009). On these lines, some researchers have tended to argue that the underlying IO/SAM models considered in economic analyses of tourism are often outdated, since databases are published only infrequently (Kronenberg et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…As Artal-Tul et al (2020) reported, the literature review by Polo and Valle (2012) is of use in highlighting several examples within the framework of an IO approach. These include country case studies, such as those by Baster (1980) for Scotland, by O’Hagan and Mooney (1983) and by Henry and Deane (1997) for Ireland, by Cooper and Pigram (1984) for Australia, by Jones and Munday (2004) for Wales, by Ünlüönen et al (2011) and Atan and Arslanturk (2012) for Turkey, by Munjal (2013) for India, and by Khanal et al (2014) for Laos.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have highlighted that despite significant potential to contribute to economic development, revenue leakages in the tourism sector have remained a key challenge (Mellor, 2003; Simata, 2019; Ünlüönen et al., 2011; Wiranatha et al., 2017). Tourism has typically been critiqued by social scientists for its exclusive nature; benefitting the privileged and marginalising the poor (Gillovic and McIntosh, 2020).…”
Section: Fiji and Tourismmentioning
confidence: 99%